npj Microgravity - Nickerson, Cheryl; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Microgravity considers all aspects of research that enables spaceflight and space exploration and the challenges of operating in space environments, including planetary surfaces. The journal covers a broad range of topics including but not limited to: Space medicine and health maintenance Biomedical responses and adaptations to space environments Human factors and psychological aspects of long-duration space missions Plant biology and growth in reduced gravity Microbial behaviour in space Fluid dynamics physics Complex fluids Fundamental physics Materials science and manufacturing In-space manufacturing In-situ resource utilization Engineering technology Space biotechnology and applications Space agriculture and food production Effects of radiation and radiation shielding in space environments Space technology and hardware development Combustion science Space biology and astrobiology Space environmental monitoring and contamination control Sustainable space exploration, environmental impact, and responsible resource management Collaborative efforts and international spaceflight and exploration partnerships The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by spaceflight experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Life sciences; Physics; Biotechnology; Immunology; Solar system; Industrial microbiology; Life Sciences; Classical and Continuum Physics; Biotechnology; Immunology; Space Physics; Industrial Microbiology